PENGARUH PENERAPAN STRATEGI PEMBELAJARAN POSTER SESSION TERHADAP HASIL BELAJAR KOGNITIF PADA MATERI RELASI DAN FUNGSI SISWA KELAS VIII MTS MATHOLI’UL HUDA TROSO - Anisa Anisa; Nanang Nabhar Fakhri Auliya (CV. ADIBA AISHA AMIRA, 2024)
The aim of this study was to find out better student cognitive learning outcomes among students using expository learning strategies and session posters. The research was conducted at MTs Matholi’ul Huda Troso. The approach used is a quantitative approach of the experimental type Quasi Experimental Design. In this study, samples were selected using purposive sampling techniques and obtained class VIII D of 32 students as a control class and class VIII E of 32 student as an experimental class. Data collection techniques performed with written documentation tests. The results of the independent t- test analysis concluded that the cognitive learning outcomes of students using the poster session learning strategy were better than those of students who used the expository learning strategy, demonstrated with a sig score of 0,00 < 0,05, t_count = 8,172 > t_table = 1,99897, as well as the average learning score obtained in the experimental class was higher than the average of the control class (79,25 > 64,78). Thus, it can be concluded, that the cognitional learning outcome of students that used the poster sessions strategy was better than the learning output of students with the expository learning strategy.